Comprehensive Physiology 2015
DOI: 10.1002/cphy.c150008
|View full text |Cite
|
Sign up to set email alerts
|

Salt, Angiotensin II, Superoxide, and Endothelial Function

Abstract: Proper function of the vascular endothelium is essential for cardiovascular health, in large part due to its antiproliferative, antihypertrophic, and anti-inflammatory properties. Crucial to the protective role of the endothelium is the production and liberation of nitric oxide (NO), which not only acts as a potent vasodilator, but also reduces levels of reactive oxygen species, including superoxide anion (O2•-). Superoxide anion is highly injurious to the vasculature because it not only scavenges NO molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 354 publications
1
32
0
Order By: Relevance
“…Accumulating evidence has demonstrated that endothelial dysfunction promotes BP elevation and serves as a bridge between angiotensin II and hypertension . In the present study, we investigated whether IL‐22 plays a role in regulating endothelial function.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Accumulating evidence has demonstrated that endothelial dysfunction promotes BP elevation and serves as a bridge between angiotensin II and hypertension . In the present study, we investigated whether IL‐22 plays a role in regulating endothelial function.…”
Section: Discussionmentioning
confidence: 95%
“…Accumulating evidence has demonstrated that endothelial dysfunction promotes BP elevation and serves as a bridge between angiotensin II and hypertension. 18,[41][42][43] In the present study, we investigated whether IL-22 plays a role in regulating endothelial function. The results showed that rIL-22 further promoted the effect of angiotensin II on endotheliumdependent and -independent relaxation responses, whereas anti-IL-22 mAb reversed the effect of angiotensin II.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are especially relevant in light of recent studies showing that HS diet leads to endothelial dysfunction in healthy normotensive male [58] and female [59] humans. In this regard, the results of the present study suggest novel therapeutic targets including not only the mas receptor but also other components of the renin-angiotensin system to treat diseases associated with salt-induced endothelial dysfunction, chronically low angiotensin II levels, and vascular oxidant stress [60]. …”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the common accepted knowledge, they propose that sufficient levels of Ang actually are essential for normal vascular function, as confirmed in the studies which have demonstrated that a decrease in the circulating levels of Ang lead to impaired microvascular endothelial function [28]. As for Ang, Kolka additionally exposes its effect on blood vessel permeability which indirectly also affects the tissue metabolism [29].…”
Section: The Central Role Of Endothelium In the Regulation Of Vasculamentioning
confidence: 97%